1975
DOI: 10.1111/j.1432-1033.1975.tb04088.x
|View full text |Cite
|
Sign up to set email alerts
|

Globin mRNA Translation on Artemia salina Ribosomes with Components from Friend Leukemia Cells

Abstract: Globin mRNA can be translated with relatively high efficiency in a fractionated cell-free system containing ribosomes prepared from cysts of Artemia salina. These ribosomes have unusually low endogenous activity for peptide synthesis in the absence of added mRNA. The system requires components from the postribosomal supernatant and from the 0.5 M KCI ribosomal wash fraction. Both these fractions were derived from either rabbit reticulocytes or unstimulated Friend leukemia cells that produce little or no hemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Enzyme activity was monitored as dose response curves, and relative activities were deduced by comparing 50% inhibitory concentrations (IC 50 ) under standard conditions. RTA was incubated for 5 min at 25 °C with 350 nM Artemia salinas ribosomes (purified as described by Kramer et al, 1975), the reaction was stopped by addition of anti-RTA antibodies, and residual ribosome activity was measured as previously described (Ready et al, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme activity was monitored as dose response curves, and relative activities were deduced by comparing 50% inhibitory concentrations (IC 50 ) under standard conditions. RTA was incubated for 5 min at 25 °C with 350 nM Artemia salinas ribosomes (purified as described by Kramer et al, 1975), the reaction was stopped by addition of anti-RTA antibodies, and residual ribosome activity was measured as previously described (Ready et al, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…Yeast tRNAPhc, either unlabeled or labeled at the S'-phosphate, was aminoacylated as previously described (Hardesty et al, 1971) except that a 0.5 M KC1 salt wash of ribosomes from rabbit reticulocytes was used as the source of synthetases. The reaction mixture, in a final volume of 1 mL, contained 50 mM Tris-HCl (pH 7.5), 20 mM Mg(OAc)2,120 mM KC1, 2.5 mM dithioerythritol, 3.75 mM ATP, 60 µ [14C]Phe (100 Ci/ mol), 10 A 260 units of tRNAPhe, and 40 µg of the 0.5 M KC1 ribosomal salt wash fraction prepared as described previously (Kramer et al, 1975). After incubation for 20 min at 37 °C, the tRNA was extracted twice with phenol and collected by ethanol precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence presented here suggests that initiation factors from uninduced FL cells have different properties in recognizing mRNA than those from differentiated normal erythroid cells. This possibility is supported by the findings of Kramer et al (28). They have shown that crude initiation factor preparations from uninduced FL cells are able to support accurate translation of rabbit globin mRNA, using Artemia salina ribosomes but at a much lower efficiency than when the rabbit reticulocyte fractions are used.…”
Section: Discussionmentioning
confidence: 67%